Association Analysis and Identification of ZmHKT1;5 Variation With Salt-Stress Tolerance - Jiang, Zhilei; Song, Guangshu; Shan, Xiaohui; Wei, Zhengyi; Liu, Yanzhi; Jiang, Chao; Jiang, Yu; Jin, Fengxue; Li, Yidan (Frontiers in Plant Science, 2018)
The high-affinity potassium transporter (HKT) genes are essential for plant salt stress tolerance. However, there have been few studies on salt stress response of HKTs in maize (Zea mays), and if natural sequence variations in these genes are associated with the phenotypic variability of salt tolerance is basically unknown. Here, we report the characterization of ZmHKT1;5, a member of HKT gene family from maize. During salt stress, ZmHKT1;5 expression increased strongly in salt-tolerant inbred lines, which accompanied a better-balanced Na+/K+ ratio and preferable plant growth. The association between nucleic acid variations in ZmHKT1;5 and salt tolerance was evaluated in a diverse population of maize consisting of 54 varieties from tropical and temperate regions. A significant association between genetic variations in ZmHKT1;5 and salt tolerance was identified. Further analysis found that two SNPs (A134G and A511G) in the coding region of ZmHKT1;5 were associated with different levels of salt tolerance among maize varieties. Moreover, a favorable allele of ZmHKT1;5, identified in the salt-tolerant maize varieties, was effective in imparting plant tolerance to salt stress. Transgenic tobacco plants of overexpressing the favorable allele displayed enhanced tolerance to salt stress better than overexpressing the wild type ZmHKT1;5. Our research showed that ZmHKT1;5 expression could effectively enhance salt tolerance by maintaining an optimal Na+/K+ balance and increasing the antioxidant activity that keeps reactive oxygen species (ROS) at a low accumulation level. Especially, the two SNPs in ZmHKT1;5 might be related with new amino acid residues to confer salt tolerance in maize.